How Do European Pharmacy Students Rank Competences for Practice? - Jeffrey Atkinson; Kristien De Paepe; Antonio Sánchez Pozo; Dimitrios Rekkas; Daisy Volmer; Jouni Hirvonen; Borut Bozic; Agnieska Skowron; Constantin Mircioiu; Annie Marcincal; Andries Koster; Keith Wilson; et al. (MDPI AG, 2016)
European students (n = 370), academics (n = 241) and community pharmacists (n = 258) ranked 13 clusters of 68 personal and patient care competences for pharmacy practice. The results show that ranking profiles for all three groups as a rule were similar. This was especially true of the comparison between students and community pharmacists concerning patient care competences suggesting that students have a good idea of their future profession. A comparison of first and fifth (final) year students shows more awareness of patient care competences in the final year students. Differences do exist, however, between students and community pharmacists. Students-like academics-ranked competences concerned with industrial pharmacy and the quality aspects of preparing drugs, as well as scientific fundamentals of pharmacy practice, well above the rankings of community pharmacists. There were no substantial differences amongst rankings of students from different countries although some countries have more "medicinal" courses than others. This is to our knowledge the first paper to look at how, within a healthcare sectoral profession such as pharmacy, the views on the relative importance of different competences for practice of those educating the future professionals and their students, are compared to the views of working professionals.